Monstrous adversary : the life of Edward de Vere, 17th Earl of Oxford - Nelson, Alan H. (Liverpool English texts and studies, 2003)
The Elizabethan Court poet Edward de Vere has, since 1920, lived a notorious second, wholly illegitimate life as the putative author of the poems and plays of William Shakespeare. The work reconstructs Oxford?s life, assesses his poetic works, and demonstrates the absurdity of attributing Shakespeare?s works to him. The first documentary biography of Oxford for over seventy years, Monstrous Adversary seeks to measure the real Oxford against the myth. Impeccably researched and presenting many documents written by Oxford himself, Nelson?s book provides a unique insight into Elizabethan society a.